Light pigmentation phenotype is correlated with increased substantia nigra echogenicity. Issue 13 (23rd September 2015) - Rumpf, Jost‐Julian; Schirmer, Maria; Fricke, Christopher; Weise, David; Wagner, Justinus Aspasios; Simon, Jan; Classen, Joseph
ABSTRACT: Objective: This study was undertaken to address the question of whether pigmentation may be mechanistically linked with Parkinson's disease. Methods: In a cross‐sectional, observational study, 116 healthy subjects received transcranial sonography of the substantia nigra. Pigmentation phenotype was assessed using the Fitzpatrick skin phototype classification, and five additional phenotypic pigmentation traits as well as a photographic method (Melanin index) in a subgroup of 46 subjects. Results: Lighter skin phototype was associated with larger echogenic substantia nigra area and increased prevalence of abnormally enlarged echogenic substantia nigra area. The strongest association of substantia nigra echogenicity and phenotypic pigmentation traits was found for hair color and facial tanning. Interpretation: Findings suggest an increasing prevalence of structural abnormality of substantia nigra with decreasing darkness of skin and thus may provide additional evidence in favor of a pathogenic link of pigmentation and Parkinson's disease. © 2015 International Parkinson and Movement Disorder Society